Section Cesarea Incidence Rate with Indication of Premature Rupture of Membrane - Lilis Candra Yanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Early rupture of membranes is one of the complicators in pregnancy and childbirth that plays a role in increasing perinatal maternal pain and death that can be caused by infection, where the amniotic membrane that is a barrier to the entry of infection-causing germs is no longer there so that it can be dangerous for the mother and fetus. The purpose of conducting research is to determine the incidence of SC with indications of premature rupture of membranes in Poso area general hospitals—descriptive research method with a Retrospective approach. The study subjects were mothers with SC delivery with hints of KPD selected using purposive sampling techniques. The results of 30 SC mothers with symptoms of Early Rupture of Water (KPD) at the Poso Regional General Hospital were dominated by mothers aged 20-35 years, primiparous parity, gestational age ≥37 weeks, and not working. It can be concluded that it cannot be ascertained that there is a relationship between maternal age and the incidence of KPD because the development or maturity of each woman's reproductive organs is not the same; other causative factors can also be seen from a psychological and financial perspective, such as mothers who experience anxiety in primigravida mothers. Gestational age also influences the older the gestational age will result in the opening of the cervix and stretching of the amniotic membrane, which affects the amniotic membrane so that it is weaker and more accessible to break. Regarding the activities of maternity mothers who work and do not work, it will not affect their health if the mother can still control rest and knows the limits of work. The cause of KPD is multifactor and is usually associated with increased physical stress that causes the amniotic membrane to become weak.